Forensic pathology reviews volume 3 - Tsokos, Michael (Forensic pathology reviews)
Maintaining the high quality achieved in earlier volumes, leading national and international forensic pathologists provide in Forensic Pathology Reviews, Volume 3 evidence-based accounts of special topics of current interest from various fields of forensic pathology and death-scene investigation. The authors offer cutting-edge insights into the medicolegal investigation of bodies found in water, the forensic aspects of the human immunodeficiency virus (HIV)-1 infection of the central nervous system, deaths in a head-down position, and forensic bitemark analysis. Additional chapters address taphonomic changes in human bodies during the early postmortem interval, arrhythmogenic ventricular dysplasia that produces sudden death in young people, the postmortem diagnosis of death in anaphylaxis, and iatrogenic deaths. The forensic aspects of suicide, murder-suicide, and suicide trends in the United States are also discussed, along with the evaluation of fatal pulmonary thromboembolism and the use of radiology in medicolegal investigations. A comprehensive, up-to-date review of the international literature is given for each chapter. Evidence-based and state-of-the-art, Forensic Pathology Reviews, Volume 3 synthesizes the practical advances made in a variety of important subspecialties of forensic pathology, demonstrating how the latest medical and scientific advances are being applied to solve current problems of high interest to forensic pathologists today. Death from environmental conditions - Macroscopical, microscopical, and laboratory findings in drowning victims - Forensic neuropathology - HIV-1 infection of the central nervous system - Forensic pathophysiology - Death in a head-down position - Forensic odontology - Bitemarks - Taphonomy - Postmortem changes and artifacts occurring during the early postmortem interval - Macroscopical findings on soil-embedded skeletal remains allowing the exclusion of a forensically relevant lay time - Death from natural causes - Right and left ventricular arrhythmogenic dysplasia - Postmortem diagnosis of anaphylaxis - Vascular conditions - The medicolegal evaluation of fatal pulmonary thromboembolism - Suicide - Trends of suicide in the united states during the 20th century - Murder-suicide - Iatrogenic injury - Iatrogenic injury - Imaging techniques in forensic pathology - Forensic radiology.